Reliability Analysis of Distribution Network Based on Reliability Index Assessment Method: A Case Study. - Putri Zulianti; Abraham Lomi; Eko Nurcahyo (International Journal of Smart Grid and Sustainable Energy Technologies, 2017)
A primary requirement of a modern electric power system is reasonable ability to satisfy the customer load requirements. Electric utilities involve generation, transmission, and distribution facilities each one of which contributes its own inherent difficulties to the problem of satisfying customer requirement. A power system should be designed and expanded the facilities in order to perform its intended function with a reasonable risk. With increasing the electrical energy demand and the potential of disruption that may occur in the system, the distribution system must have high reliability and continues supply to customer. In this case, the reliability of the distribution system needs to be evaluated by monitoring and analyzing the level of distribution system failure in a certain period of time. A study on a practical distribution system with application of automatic circuit reclosers (ACRs) which plays an important role in enhancing the reliability index of system is presented. The reliability index assessment analyze the reliability index of the existing system before and after application of ACRs. From the simulation point of view, the system average interruption frequency index (SAIFI) is about 19.43% or decreased the failure frequent event from 11.4 failure/ customer.year to 9.25 failure/customer.year); while the momentary average interruption frequency index (MAIFI) has decreased from 6.72 failure/customer.year to 5.05 failure/ customer.year, or increase the reliability index of about 24.85%.